Myocardial Perfusion Imaging After Severe COVID-19 Infection Demonstrates Regional Ischemia Rather Than Global Blood Flow Reduction - Thornton, George D.; Shetye, Abhishek; Knight, Dan S.; Knott, Kris; Artico, Jessica; Kurdi, Hibba; Yousef, Souhad; Antonakaki, Dimitra; Razvi, Yousuf; Chacko, Liza; Brown, James; Patel, Rishi; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Acute myocardial damage is common in severe COVID-19. Post-mortem studies have implicated microvascular thrombosis, with cardiovascular magnetic resonance (CMR) demonstrating high prevalence of myocardial infarction and myocarditis-like scar. The microcirculatory sequelae remain uncharacterized. Perfusion CMR can quantify stress myocardial blood flow (MBF) and identify its association with infarction and myocarditis. Aims: To determine the impact of severe, hospitalized COVID-19 on global and regional myocardial perfusion in recovered patients. Methods: Case-control study of previously hospitalized, troponin positive COVID-19 patients. Results were compared to a propensity-matched, pre-COVID chest pain cohort (referred for clinical CMR; angiography subsequently demonstrating unobstructed coronary arteries) and 27 healthy volunteers (HV). Analysis used visual assessment for regional perfusion defects and AI-based segmentation to derive global and regional stress and rest MBF. Results: 90 recovered, post-COVID patients (median age 64 [IQR 54-71] years, 83% male, 44% requiring ICU) underwent adenosine-stress perfusion CMR at a median 61 (IQR 29-146) days post-discharge. Mean LVEF was 67±10%; 10 (11%) with impaired LVEF, 50 patients(56%) had late gadolinium enhancement (LGE); 15 (17%) had infarct-pattern, 31 (34%) had non-ischemic, 4 (4.4%) mixed pattern LGE. Thirty-two patients (36%) had adenosine-induced regional perfusion defects, 26/32 with at least 1 segment without prior infarction. Global stress MBF in post-COVID patients was similar to age-, sex- and co-morbidities matched controls (2.53±0.77 vs 2.52±0.79ml/g/min, p=0.10), though lower than HV (3.00±0.76 ml/g/min, p<0.01). Conclusions: After severe hospitalized COVID-19 infection, patients attending for clinical ischemia testing have little evidence of significant microvascular disease at 2 months post